The Optimization of transport route from Chon Buri, Thailand to Kunming, China by using AHP and TOPSIS - Netirith, Narthsirinth (Naresuan University Journal: Science and Technology (NUJST); Vol 29 No 4 (2021): October-December 2021, 2021)
This research paper studies the optimal routes in intermodal transportation between Chonburi, Thailand to Kunming, China since Kunming has become one of the trade centers in China and located close to Thailand. Also both countries have a challenging development in  transport network connectivity. Currently, the route between Thailand and China have been limited because the route still lack the missing link, some routes are under construction, and routes in the future of national transportation plan. However, this study will assume for the future transport route that the missing links have been connected, the under construction routes have been completed This actions will increase the number of alternatives. Then this paper will consider the ideal route for transporting the freight. The route selection process examines 5 current routes and also considers 5 future routes to determine optimal of intermodal transport route which only road and rail transportation are analyzed. Regarding the criteria on there are quantitative factors (Transportation time, Transportation distance, Transportation cost) and the qualitative factors (Level of difficulty for transportation, Transport congestion, Opportunity for revenue) of with total 6 main criteria and 7 in sub-criteria, the most efficient transport route should be at the lowest cost, shortest distance and least transport time. Also Transportation belong this route should consider a good infrastructure, smooth transport flow and less congestion also it have a good change to making a business and revenue. On the other hand,  the criteria have been weighed and selected by establishment with a mathematic model based on Analytical Hierarchy Process (AHP). The final phase using TOPSIS to optimize the route based on the weight. The results showed that route number 2, from Chonburi to Mae Sai, Chiang Rai in Thailand then to Xishuangbanna direct to Kunming, have a total distance in 1610 km with the travel time of 32 hours and the total cost is 13497.38 Baht. Therefore, is the ideal route for transportation with the highest TOPSIS score 0.876. Keywords: Route selection, TOPSIS, Multicriteria decision, AHP